Current account deficits and sustainability: evidence from South Africa - Ngakaagae, Lee Zwangu (School of Economics, 2025)
This paper investigates current account sustainability in South Africa using stationarity and coin tegration approaches to assessing intertemporal solvency - where intertemporal solvency implies current account sustainability. The contribution in this paper are four-fold. First, we consider a key emerging market, South Africa, that runs persistent current account deficits that might leave the economy vulnerable to macroeconomic destabilisation. Second, the study utilises both stationarity and cointegration approaches for a consensus in results, where existing literature uses one or the other. Third, this study considers nonlinear methods in its evaluation, and to our knowledge, all studies evaluating South Africa, and most global literature, rely on linear methods. Lastly, we use three specifications of the current account in the cointegration approach for robust results, whereas existing studies tend to use a single specification. Stationarity of the current account to GDP ratio is assessed through linear unit toot tests; ADF, PP, KPSS, DFGLS, ZA unit root tests, and nonlinear KSS (ESTAR) and Sollis (AESTAR) unit root tests. The cointegration approach relies on the linear Engle-Granger, Johansen, Maki, ARDL tests, and nonlinear ARDL (NARDL) tests, on exports - imports, and investments – savings variables. The tests are applied to three data samples for robust results: annual data between 1946-2021, full quarterly data 1960Q1-2021Q4, and short quarterly data 1985Q3-2021Q4. The study consistently finds mean reversion properties through linear unit root tests on annual and full quarterly data. Contrastingly, sustainability cannot be established through linear unit root tests for the short quarterly data but is established through nonlinear KSS (ESTAR) and Sollis (AESTAR) unit root tests. This finding suggests that the current account to GDP ratio of South Africa is a nonlinear but stationary process in the short term. Furthermore, we consistently find cointegration in annual data through the Engle-Granger and Johansen tests, while cointegration is only found when incorporating breaks through the Maki test for quarterly data. Based on the DOLS and ARDL estimators, we are able to find evidence of strong current account sustainability. Still, this result is highly dependent on sample, current account components under consideration, and model specification, with short quarterly data resulting in a non-sustainability conclusion, whereas annual data over a longer time frame gives a sustainability conclusion. Lastly, we find evidence of asymmetric cointegration on utilising the NARDL on short quarterly data, with the conclusion that the current account is sustainable when asymmetries are considered.